A highly sensitive biosensing platform based on upconversion nanoparticles and graphene quantum dots for the detection of Ag+. (5th May 2017) - He, Lu; Yang, Lin; Zhu, Hao; Dong, Wenkui; Ding, Yujie; Zhu, Jun-Jie
Abstract: A novel luminescence 'Turn-On' nanoplatform for the sensitive sensing of Ag + was fabricated based on luminescence resonance energy transfer technique between sodium citrate functionalized upconversion nanoparticles (Cit-UCNPs, energy donor) and graphene quantum dots (GQDs, energy acceptor). Amino-labeled single-stranded DNA (NH2 -ssDNA) containing a number of cytosine (C) was conjugated on the surface of the Cit-UCNPs to capture Ag + ions. Due to the π – π stacking interaction between NH2 -ssDNA and GQDs, the upconversion luminescence can be quenched. However, upon the addition of Ag +, the π – π stacking interaction weakens due to the formation of the hairpin structure of C–Ag + –C on the UCNPs. As a result, GQDs will leave the surface of the UCNPs and the upconversion luminescence can be enhanced (Turn-On). Based on this fact, the sensor was developed for the detection of Ag + with a linear concentration range from 2 × 10 −4 to 1 μ M and a detection limit as low as 60 pM. The assay method is fairly simple with high selectivity and sensitivity, which can be used for the determination of Ag + in environmental water samples.